The cost of consent: why healthcare providers must be compliant with the Montgomery principles. (May 2020) - Birch, Nick; Todd, Nick V.
Abstract : The cost of clinical negligence in the UK has continued to rise despite no increase in claims numbers from 2016 to 2019. In the US, medical malpractice claim rates have fallen each year since 2001 and the payout rate has stabilized. In Germany, malpractice claim rates for spinal surgery fell yearly from 2012 to 2017, despite the number of spinal operations increasing. In Australia, public healthcare claim rates were largely static from 2008 to 2013, but private claims rose marginally. The cost of claims rose during the period. UK and Australian trends are therefore out of alignment with other international comparisons. Many of the claims in orthopaedics occur as a result of "failure to warn", i.e. lack of adequately documented and appropriate consent. The UK and USA have similar rates (26% and 24% respectively), but in Germany the rate is 14% and in Australia only 2%. This paper considers the drivers for the increased cost of clinical negligence claims in the UK compared to the USA, Germany and Australia, from a spinal and orthopaedic point of view, with a focus on "failure to warn" and lack of compliance with the principles established in February 2015 in the Supreme Court in the case of Montgomery v Lanarkshire Health Board. The article provides a description of the prevailing medicolegal situation in the UK and also calculates, from publicly available data, the cost to the public purse of the failure to comply with the principles established. It shows that compliance with the Montgomery principles would have an immediate and lasting positive impact on the sums paid by NHS Resolution to settle negligence cases in a way that has already been established in the USA. Cite this article: Bone Joint J 2020;102-B(5):550–555.